BIOFILIA DAN NEKROFILIA: ANALISIS SOSIOLOGI SASTRA NOVEL LA BÊTE HUMAINE KARYA EMILE ZOLA - Ali Shahab (Universitas Gadjah Mada, 2011)
Using the genetic structural analysis suggested by Lucien Goldmann, it has been shown that Emile Zola, an adherent of naturalism, has managed to expose a distinctive world view through the mediation of his work bring La bête humaine. Through his career as an author who fully engaged in the social and political life of his time, Zola firmly demonstrated a world view different than contemporary rulers. His involvement in the political field, his support and empathy for the weak who became victims of an unjust capitalist system, and his commitment to the truth in which he believed, produced changes in the social and political fields. This is evident from the contemporary recognition of social rights of workers and the release of Alfred Dreyfus from prison. Yet for all that he paid with his life; Zola was assassinated by political opponents.